Mass dependence of the deconfinement and chiral restoration critical temperatures in nonlocal SU(2) Polyakov-Nambu-Jona-Lasinio models - Pagura, Valeria Paula (2013)
In the framework of nonlocal SU(2) chiral quark models with Polyakov loop, we analyze the dependence of the deconfinement and chiral restoration critical temperatures on the explicit chiral symmetry breaking driven by the current quark mass. Our results are compared with those obtained within the standard local Polyakov-Nambu-Jona-Lasinio model and with lattice QCD calculations. For a wide range of pion masses, it is found that both deconfinement and chiral restoration critical temperatures turn out to be strongly entangled, in contrast with the corresponding results within the Polyakov-Nambu-Jona-Lasinio model. In addition, it is seen that the growth of the critical temperatures with the pion mass above the physical point is basically linear, with a slope parameter that is close to the existing lattice QCD estimates. On the other hand, we find a tendency to favor an early onset of the first order transition expected in the large quark mass limit.